A Quantitative Analysis of Latino Acculturation and Alcohol Use: Myth Versus Reality. (14th June 2017) - Alvarez, Miriam J.; Frietze, Gabriel; Ramos, Corin; Field, Craig; Zárate, Michael A.
Abstract : Research on health among Latinos often focuses on acculturation processes and the associated stressors that influence drinking behavior. Given the common use of acculturation measures and the state of the knowledge on alcohol‐related health among Latino populations, the current analyses tested the efficacy of acculturation measures to predict various indicators of alcohol consumption. Specifically, this quantitative review assessed the predictive utility of acculturation on alcohol consumption behaviors (frequency, volume, and quantity). Two main analyses were conducted—a p‐curve analysis and a meta‐analysis of the observed associations between acculturation and drinking behavior. Results demonstrated that current measures of acculturation are a statistically significant predictor of alcohol use ( Z  = −20.75, p  <   0.0001). The meta‐analysis included a cumulative sample size of 29, 589 Latino participants across 31 studies. A random‐effects model yielded a weighted average correlation of 0.16 (95% confidence interval = 0.12, 0.19). Additional subgroup analyses examined the effects of gender and using different scales to measure acculturation. Altogether, results demonstrated that acculturation is a useful predictor of alcohol use. In addition, the meta‐analysis revealed that a small positive correlation exists between acculturation and alcohol use in Latinos with a between‐study variance of only 1.5% ( τ 2  = 0.015). Our analyses reveal that the association between current measures of acculturation and alcohol use is relatively small. Abstract : This review investigated how effective measures of acculturation are at predicting drinking behaviors (quantity, frequency, and volume). Results revealed the effects of acculturation on drinking behaviors were relatively small. Sub‐analysis found that the association between acculturation and alcohol use in Latinos was greater in women than in men, and that language use was the strongest and most effective predictor of acculturation and drinking behaviors. These findings provide a strong argument against treating acculturation as a uniform process.